Penggunaan Metode Hybrid e-Learning untuk Praktikum Imunologi Farmasi di Fakultas Farmasi Universitas Gadjah Mada - Ikawati, Muthi'; Hermawan, Adam; Sahid, Muhammad Novrizal Abdi; Kristina, Susi Ari; Sasmito, Ediati (Pusat Penelitian dan Pengembangan Biomedis dan Teknologi Dasar Kesehatan, 2021)
Laboratory work of Pharmaceutical Immunology, Faculty of Pharmacy UGM aims to provide skills of applying antigens, antibodies, and immunological techniques in pharmaceutical; and ideally each student should be able to perform it completely. However, the limitation of time and facilities making the learning process ineffective. An innovative learning method such as hybrid e-learning is expected to increase the learning effectiveness. Learning materials and online quizzes/discussions were uploaded and carried out using elisa.ugm.ac.id (eLisa), respectively, combined with on-site works in the laboratory. The method was evaluated by examination scores and final grades. Student participations in online quizzes increased from first to fourth quiz (average participation rate 98.86±0.87%). Compared to the conventional method applied in 2016 (n=207), the examination average score did not increase; however, the percentage of students whose score is 90-100 were higher in the hybrid e-learning. The average final grade of the hybrid e-learning was 81.43±0.70; whereas the conventional method of 2016 was 80.22±5.22. More than 80% students (n=48) expressed easiness in following courses and were satisfied with the online learning materials’ quality. Hence, the hybrid e-learning results positive effects in increasing the effectiveness of the learning process. Development of more interactive online platforms is needed to optimize the learning process.